ANALISIS IMPLEMENTASI PENGEMBANGAN PEMBELAJARAN BERBASIS HOTS DALAM KURIKULUM 2013DI SEKOLAH DASAR - Enjelika Palinoaz; Regina Mulyasari (Yayasan Citra Dharma Cindekia, 2025)
In learning, there must be a method of interaction between students and educators and learning resources during a learning setting. Education mutually of the parameters of the progress of a nation becomes important with human resources because the benchmark. The objectives of this study are: Changes within the 2013 revised course of study need academics to be able to structure and implement learning, methods for getting ready HOTS queries area unit administered by involving all elements and coaching grammar school students' psychological feature skills. Competition in science is progressively being administered by the international community, so country is additionally needed to be able to contend globally so as to boost the dignity of the state. Therefore, to face the challenges that may befall the planet of education, the 2013 course of study is taken into account capable of responsive these issues and therefore the implementation of HOTS is required to boost instructional performance that is much behind developed countries within the world. The instruments employed in this study will be obtained from many studies from many journals. With qualitative analysis strategies. The results of the journal review that we've got done is that the implementation of HOTS-based learning development within the 2013 course of study still must be improved, seeing from a number of the analysis results that we have a tendency to reviewed as several as ten journals, the extent of student mastery isn't maximized.